2016
DOI: 10.1002/ldr.2580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Development Time and Litter Quality on Soil Carbon Sequestration: Assessing Soil Carbon Saturation with a Field Transplant Experiment along a Post‐mining Chronosequence

Abstract: In previous studies, the rate of soil carbon (C) sequestration decreased with increasing age of post‐mining soils. It was also shown to depend on plant biomass and earthworm bioturbation. Here, a soil transplant experiment was used to determine whether this decrease is caused by soil C saturation or other factors (such as bioturbation and litter input). Soils collected on 15‐, 25‐ and 50‐year‐old successional sites, dominated by willow (Salix caprea L.) and birch (Betula pendula Roth), and on a 50‐year‐old sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…This was simply because overall plant biomass was larger in developed soil than in young soil. A similar pattern was reported for the rate of soil organic matter accumulation, which was in absolute values low in undeveloped overburden substrates, which then increased in soils that were being affected by plants and soil fauna in early to midsuccession and which then decreased in a mature soil near carbon saturation (Frouz, 2017). Previous studies have reported that the effect of earthworms on plants may depend on the soil conditions (Laossi, Decaëns, Jouquet, & Barot, 2010).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This was simply because overall plant biomass was larger in developed soil than in young soil. A similar pattern was reported for the rate of soil organic matter accumulation, which was in absolute values low in undeveloped overburden substrates, which then increased in soils that were being affected by plants and soil fauna in early to midsuccession and which then decreased in a mature soil near carbon saturation (Frouz, 2017). Previous studies have reported that the effect of earthworms on plants may depend on the soil conditions (Laossi, Decaëns, Jouquet, & Barot, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…Earthworms modify the structure and chemical composition of soil (Bottinelli et al, 2015). By bioturbation they stabilize organic matter in soil and form soil aggregates (Angst et al, 2017;Bottinelli et al, 2015;Frouz, 2017). Such changes generally increase soil water holding capacity, soil nutrient content and plant productivity (Bottinelli et al, 2015;Lavelle et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration of the biological and hydrological cycles after land abandonment results in recovery of soil carbon stocks as found by other studies when land was abandoned (Brevik and Lazari, 2014), forests were transformed into crops (Wasak and Drewnik, 2015), or when degraded rangelands were restored (Zucca et al, 2016). There is a positive interaction in the soil system after abandonment that favours the recovery of the biota (fauna and flora) followed by litter and organic matter, which finally improves soil quality and as a consequence the diversity and mass of the biota (Certini et al, 2015;Chen et al, 2016;Frouz, 2016).…”
Section: Soc Stock and Soc After Abandonment In Each Soil Region And mentioning
confidence: 76%
“…Improvement of soil quality and selection of suitable vegetation in reclaimed land plays an important role in enhancing the carbon sequestration potential in mining areas. Soil organic matter in the early stage of the reclamation process is very important for the recovery of SOC in the late stage of mining and the carbon sequestration capacity will be strengthened over time [51,52].…”
Section: The Impact Of Vegetation Type and Soil Quality On Carbon Seqmentioning
confidence: 99%